Kemampuan Antagonistik Beberapa Isolat Pseudomonad Fluoresen Terhadap Bakteri Ralstonia Solanacearum Penyebab Penyakit Layu Pada Tanaman Tomat - Yenny WURYANDARI; Arika PURNAWATI; Triwidodo ARWIYANTO; Bambang HADISUTRISNO (Jurnal Pengendalian Hayati, 2008)
Bacterial Wilt disease (Ralstonia solanacearum) is a main problem in tomato plant.Controls of it have been optimum success yet. Control of it using certainly pseudomonad fluorescentstrain can pressure plant disease developments which cause soil pathogen.The aim of the research, getpseudomonad fluorescent from tomato rizosfer which can inhibit of wilt bacteria disease Ralstoniasolanacearum. Research methods are isolation and identification of pathogen bacteria andantagonistic bacteria. Biological control agents candidate selection was done with antagonistic invitro and inhibit mechanism test. The Research show; there is wilt symptom in tomato areal at WajakMalang. From isolation get Ralstonia solanacearum bacteria with identity white coloni, fluidal,irregular shape in YPGA media and high virulensi. From tomato rizosfer soil isolation in the sameareal get 130 isolate of pseudomonad fluorescent in King’s B media. Antagonistec test in vitro to itisn’t of all bacteria can inhibit Ralstonia solanacearum growing. From them which was tested, getvariation of inhibit zona from 4 mm until more than 30 mm. More of inhibit mechanism isbacteriostatic and only many is bacterisida.